Concept relationships in knowledge organization systems: Elements for analysis and common research among fields - Moreira, Walter [UNESP]; Martínez-Ávila, Daniel [UNESP] (Taylor & Francis, 2018)
Knowledge organization systems have been studied in several fields and for different and complementary aspects. Among the aspects that concentrate common interests, in this article we highlight those related to the terminological and conceptual relationships among the components of any knowledge organization system. This research aims to contribute to the critical analysis of knowledge organization systems, especially ontologies, thesauri, and classification systems, by the comprehension of its similarities and differences when dealing with concepts and their ways of relating to each other as well as to the conceptual design that is adopted.
Keywords: Concept relationships; Knowledge organization systems; Ontologies; Thesauri